How Linux works : what every superuser should know - Ward, Brian (No Starch Press, 2004)
How Linux Works describes the inside of the Linux system for systems administrators, whether they maintain an extensive network in the office or one Linux box at home. After a guided tour of filesystems, the boot sequence, system management basics, and networking, author Brian Ward delves into topics such as development tools, custom kernels, and buying hardware. With a mixture of background theory and real-world examples, this book shows both how to administer Linux, and why each particular technique works, so that you will know how to make Linux work for you.